Comparative Transcriptomics and Proteomics of Atractylodes lancea in Response to Endophytic Fungus Gilmaniella sp. AL12 Reveals Regulation in Plant Metabolism - Yuan, Jie; Zhang, Wei; Sun, Kai; Tang, Meng-Jun; Chen, Piao-Xue; Li, Xia; Dai, Chuan-Chao (Frontiers in Microbiology, 2019)
The fungal endophyte Gilmaniella sp. AL12 can establish a beneficial association with the medicinal herb Atractylodes lancea, and improve plant growth and sesquiterpenoids accumulation, which is termed “double promotion”. Our previous studies have uncovered the underling primary mechanism based on some physiological evidences. However, a global understanding of gene or protein expression regulation in primary and secondary metabolism and related regulatory processes is still lacking. In this study, we employed transcriptomics and proteomics of Gilmaniella sp. AL12-inoculated and Gilmaniella sp. AL12-free plants to study the impact of endophyte inoculation at the transcriptional and translational levels. The results showed that plant genes involved in plant immunity and signaling were suppressed, similar to the plant response caused by some endophytic fungi and biotroph pathogen. The downregulated plant immunity may contribute to plant-endophyte beneficial interaction. Additionally, genes and proteins related to primary metabolism (carbon fixation, carbohydrate metabolism and energy metabolism) tended to be upregulated after Gilmaniella sp. AL12 inoculation, which was consistent with our previous physiological evidences. And, Gilmaniella sp. AL12 upregulated genes involved in terpene skeleton biosynthesis, and upregulated genes annotated as β-farnesene synthase and β-caryophyllene synthase. Based on the above results, we proposed that endophyte-plant associations may improve production (biomass and sesquiterpenoids accumulation) by increasing the source (photosynthesis), expanding the sink (glycolysis and tricarboxylic acid cycle), and enhancing the metabolic flux (sesquiterpenoids biosynthesis pathway) in Atractylodes lancea. And, this study will help to further clarify plant-endophyte interactions.